2020
DOI: 10.1038/s41598-020-64515-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of murine macrophages stimulated with cartilage fragments revealed a strategy for treatment of progressive osteoarthritis

Abstract: Accumulating evidence suggests that synovitis is associated with osteoarthritic process. Macrophages play principal role in development of synovitis. Our earlier study suggests that interaction between cartilage fragments and macrophages exacerbates osteoarthritic process. However, molecular mechanisms by which cartilage fragments trigger cellular responses remain to be investigated. Therefore, the current study aims at analyzing molecular response of macrophages to cartilage fragments. To this end, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
1
18
0
1
Order By: Relevance
“…In fact, the presence of inflammatory cytokines in the synovium provokes cartilage breakage and the resulting fragments/tears can then cause further pathological changes ( Macfarlane et al, 2019 ; Hamasaki et al, 2019 ). Consistent with these findings, our earlier studies demonstrated that cartilage fragments elucidate a robust inflammatory response in macrophages that are associated with increased catabolism in cartilages ( Hamasaki et al, 2019 , Hamasaki et al, 2020 ). Therefore, investigating the intercellular communication within the joint microenvironment namely between cells that reside in the synovium and cartilage would be expected to provide clues for development of a novel treatment.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…In fact, the presence of inflammatory cytokines in the synovium provokes cartilage breakage and the resulting fragments/tears can then cause further pathological changes ( Macfarlane et al, 2019 ; Hamasaki et al, 2019 ). Consistent with these findings, our earlier studies demonstrated that cartilage fragments elucidate a robust inflammatory response in macrophages that are associated with increased catabolism in cartilages ( Hamasaki et al, 2019 , Hamasaki et al, 2020 ). Therefore, investigating the intercellular communication within the joint microenvironment namely between cells that reside in the synovium and cartilage would be expected to provide clues for development of a novel treatment.…”
Section: Introductionsupporting
confidence: 82%
“…Under this condition, the production of proinflammatory cytokines in the synovium alter the chondrogenic phenotype and induce differentiation, hypertrophy and apoptosis leading to cartilage degeneration ( Abramson et al., 2006 , De Lange-Brokaar et al, 2012 ). In fact, our earlier findings, using cocultured chondrocytes model, demonstrated that cartilage fragments activate NF-κB signaling in macrophages resulting in the production of inflammatory cytokines that mediate the production of catabolic factors in chondrocytes ( Hamasaki et al., 2019 , 2020 ). Therefore, it is very important to study the molecular changes in chondrocytes that are cocultured with cartilage fragment-stimulated macrophages as a step toward developing a deeper understanding of synovium-cartilage crosstalk in the OA process.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations